(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
In democratic countries, attaining gender equality and promoting sustainable development depend on women’s ability to participate in politics. Despite women’s social and economic advancements, they are still under-represented in political leadership roles in India, the biggest democracy in the world. The historical, legal, and sociopolitical aspects that have shaped women’s involvement in Indian politics are examined in this review study. Political parties’ roles in influencing female leadership, changes in parliamentary representation, and the effects of constitutional revisions are all covered. Systemic obstacles include patriarchal institutions, prejudices within political parties, and socio-economic restraints still impede advancement, despite constitutional protections and legislative efforts to increase women’s participation. In order to increase women’s political engagement in India, this article stresses the necessity of affirmative action, changes to the law, and cultural changes.